2009
DOI: 10.1021/np9006298
|View full text |Cite
|
Sign up to set email alerts
|

Antiestrogenic Constituents of the Thai Medicinal Plants Capparis flavicans and Vitex glabrata

Abstract: Antiestrogenic compounds were investigated from Thai indigenous plants for galactogogues since estrogen is reported to suppress lactation in breastfeeding women. The aerial parts of the Thai medicinal plant Capparis flavicans, which has traditionally been used to promote lactation, gave the new compound capparoside A (1), along with 28 known compounds. The leaves of Vitex glabrata belong to the same genus as the chaste tree (Vitex agnus-castus), which is used traditionally to support lactation, and afforded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 44 publications
0
34
0
1
Order By: Relevance
“…However, the side effects (including diarrhea, flatulence, bloating, nausea, and soft feces in colon) associated with many of these antidiabetic agents as well as the high cost have limited the success rate of these drugs. [21] [22] The ethanol extracts from the leaves have been reported to have anti-inflammatory, antiestrogenic, antioxidant, and hepatoprotective activities. The World Health Organization (WHO) recommended the use of natural products based on traditional knowledge and encourages the development of herbal medicinal products for primary health care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the side effects (including diarrhea, flatulence, bloating, nausea, and soft feces in colon) associated with many of these antidiabetic agents as well as the high cost have limited the success rate of these drugs. [21] [22] The ethanol extracts from the leaves have been reported to have anti-inflammatory, antiestrogenic, antioxidant, and hepatoprotective activities. The World Health Organization (WHO) recommended the use of natural products based on traditional knowledge and encourages the development of herbal medicinal products for primary health care.…”
Section: Introductionmentioning
confidence: 99%
“…[11] [12] Natural products especially traditional herbal plants have been considered as a suitable beneficial option for the treatment of diabetes. [21][23] [24] Previous phytochemical studies of this plant have reported the presence of ecdysteroids, 11a,20-dihydroxyecdysone, 7-dehydrocholesterol, pterosterone, and 20-hydroxyecdysone isolated from the bark and khainaoside A, khainaoside B, and khainaoside C isolated from the leaves of the plant. [13] In addition, WHO has also encouraged the use of traditional medicinal plants for the treatment of diabetes due to their effectiveness and safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 8 was identified as princepin from the literature [19]. Princepin showed potent inhibitory effects on estrogen-enhanced cell proliferation [23].…”
Section: Resultsmentioning
confidence: 99%
“…[33] Similarly, its aromatic plant extract showed significant stimulating effect on melanogenesis in B16 murine melanoma cells at very low doses (0.0005, 0.005, and 0.05% w/v) without causing cytotoxicity. [34] It may be due to presence of quercetin compound, a well known melanogenesis stimulator that also increases tyrosinase protein expression.…”
Section: Anti-cancer Activitymentioning
confidence: 94%